Assessing burnout, coping mechanisms and factors relating to job satisfaction in caregivers and social workers in Singapore - Tan, Vanessa Yu Qing (2016)
This study seeks to address the challenges that social workers face on a daily basis, as well as explore various factors that contribute to an individual’s stress and eventual burnout in this field of social-care. Repeated research has shown that burnout is often associated with emotional fatigue, higher intentions to quit one’s job, and consequently poorer quality of care provided. This study also plans to assess how these challenges affect the personal well-being of mental health social workers. Various coping suggestions are provided for the prevention or minimization of burnout, with the aim of enhancing quality of care and personal well- being. Pearson Correlation is used to assess the nature and strength of relationship between Job Satisfaction and Coping Mechanisms with Burnout. Multiple Linear Regression is used to examine the strength of measures in predicting each subscales of burnout. The results indicated that all subscales of Job Satisfaction had a significant negative correlation with all subscales of Burnout. For Coping Mechanisms, only the subscale of Decreased Personal Achievement had a significant negative correlation with Appropriate Skills. As for Regression, all variables were found to be insignificant. Only the predictor variable of Social Relationship on Emotional Fatigue, and predictor variable of Appropriate Skills on Decreased Personal Achievement, were found to be trending towards significance. In implementing future policies subsequent to reducing burnout, overall job satisfaction should be carefully examined. Attention can be placed on introducing appropriate skills to social workers to help prevent them from facing decreased personal achievement.